2021
DOI: 10.1097/md.0000000000027785
|View full text |Cite
|
Sign up to set email alerts
|

APOL1 renal risk variants are associated with obesity and body composition in African ancestry adults

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…Third, regarding kidney disease risk, we showed an association with obesity and two APOL1 risk alleles but no demonstrable effect of obesity on the association of APOL1 with albuminuria. Our findings corroborate those of a similar-sized study of 11,930 African American participants, where each risk allele was associated with greater obesity odds (1.13-fold) (42), but this association has not been demonstrated in other large cohorts, such as the Coronary Artery Risk Development in Young Adults and the Atherosclerosis Risk in Communities studies (19,43). There was no effect of socioeconomic status on the association between APOL1 and albuminuria.…”
Section: Discussionsupporting
confidence: 89%
“…Third, regarding kidney disease risk, we showed an association with obesity and two APOL1 risk alleles but no demonstrable effect of obesity on the association of APOL1 with albuminuria. Our findings corroborate those of a similar-sized study of 11,930 African American participants, where each risk allele was associated with greater obesity odds (1.13-fold) (42), but this association has not been demonstrated in other large cohorts, such as the Coronary Artery Risk Development in Young Adults and the Atherosclerosis Risk in Communities studies (19,43). There was no effect of socioeconomic status on the association between APOL1 and albuminuria.…”
Section: Discussionsupporting
confidence: 89%
“…Further, obesity prevalence rates differ significantly by race and ethnicity, with African Americans being 50% more likely to be obese than non-Hispanic whites [ 44 ], and African American children are at higher risk of being obese [ 45 , 46 , 47 ]. These results are in consistence with another study, affirming that AA is at a higher risk of obesity [ 48 ] and that race, along with the BMI status, is linked with DNA methylation of genes.…”
Section: Discussionmentioning
confidence: 99%
“…Both the Jackson Health Study and the Women’s Health Initiative found that adult participants with two high-risk APOL1 alleles had an increased cardiovascular disease risk after correcting for traditional risk factors and CKD as compared with those without the high-risk alleles 26. High-risk variants were associated with BMI and obesity in an additive manner in a genotype-phenotype association study 27. Since APOL1 is an important component of HDL 3 particles that attenuate LDL oxidation, it may play a role in reverse cholesterol transport.…”
Section: Discussionmentioning
confidence: 99%